(untitled) (Bangladesh Medical Journal, 2021)
Autoimmune hepatitis (AIH) is the disease of immune mediated inflammation of liver. Presentation of AIH in children is variable, ranging from acute hepatitis to cirrhosis of liver and also as only asymptomatic raised ALT. AIH can present at any age and female are more affected. Here we are presenting two cases. Case 1 presented with jaundice and H/O epistaxis, having cutaneous echymosis, hepato-splenomegaly and ascites. Case 2 was a diagnosed case of Systemic Lupus Erythematosus (SLE) presented with only persistent raised of serum ALT. Both were diagnosed as autoimmune hepatitis on the basis of positive auto antibodies, histopathology of liver tissues and exclusion of all other causes of acute and chronic hepatitis. Bangladesh Med J. 2020 Jan; 49 (1): 45-50